The influence of social media, social engagement and volunteerism towards university's youth leadership participation in east coast, Malaysia: A conceptual paper - A.R. Syaidatull Erni Zakiah; Razli Che Razak; Derweanna Bah Simpong (Medwell Journals, 2016)
Youth leadership is teens practicing themselves on how to be a leader and how they can use their authority or power to influence other people. Youth has the potential in which they can easily gain skills and knowledge necessary to lead civic engagement, education reform, community organizing activities and others. However, through careful observation, we can see that Malaysian youth does not actively participate in leadership activities. They behave like that because they have less trust and support to be a leader from the people around them. This conceptual study aims to analyze the influence of social media, social engagement and volunteerism towards university’s youth leadership participation in East Coast, Malaysia. This study intends to adopt a quantitative survey by use of questionnaires and a cluster sampling method to collect data. University students age 18-25 year are the target population for the present study. The result of this study will help communities and government in handling issues regarding the youth generation in Malaysia.